2018
DOI: 10.1039/c7ra11364a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beta-sitosterol and its derivatives on depression by the modification of 5-HT, DA and GABA-ergic systems in mice

Abstract: Beta-sitosterol and its derivatives exhibit antidepressant-like activity mediated by the modification of 5-HT, DA and GABA-ergic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…We found that 5 R-enriched OTUs which belong to family Lachnospiraceae , were positively correlated with stigmasterol. The antidepressant effects of stigmasterol, and the effects on neurotransmitter systems and mechanisms involved in antidepressant effects have been observed 42 . Stigmasterol was found to be resistant to bacterial saturation or degradation, however, the metabolic mechanisms associated with gut microbiota are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 5 R-enriched OTUs which belong to family Lachnospiraceae , were positively correlated with stigmasterol. The antidepressant effects of stigmasterol, and the effects on neurotransmitter systems and mechanisms involved in antidepressant effects have been observed 42 . Stigmasterol was found to be resistant to bacterial saturation or degradation, however, the metabolic mechanisms associated with gut microbiota are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, β-sitosterol exhibits antidepressant and anxiolytic effects (179) (273), possibly mediated through serotonergic, GABAergic and dopaminergic mechanisms. Furthermore, phytosterols modulate the activity of endogenous steroid receptors.…”
Section: Phytosterol Impact On the Microbiota-gut-brain Axismentioning
confidence: 99%
“…On the one hand, a mouse model with vastly increased phytosterol levels from birth did not present any apparent memory or anxiety phenotypes, 49 while, on the other hand, several studies have reported pro-explorative or antidepressant properties of crude or partly purified plant sterols when administered intraperitoneally. [50][51][52] Our findings establish b-sitosterol as the only specific and robust anxiolytic from a battery of closely related phytosterols, providing a possible explanation for the conflicting reports on activities of mixed phytosterol extracts summarized above. Moreover, we show that b-sitosterol can synergize with subtherapeutic doses of the SSRI fluoxetine.…”
Section: Discussionmentioning
confidence: 53%